Metal–Organic Framework Photonic Balls: Single Object Analysis for Local Thermal Probing. Issue 43 (5th September 2021) - Avci, Civan; De Marco, Maria Letizia; Byun, Caroline; Perrin, Jonathan; Scheel, Mario; Boissière, Cédric; Faustini, Marco
Abstract: Due to their high porosity and chemical versatility, metal–organic frameworks (MOFs) exhibit physical properties appealing for photonic‐based applications. While several MOF photonic structures have been reported, examples of applications thereof are mainly limited to chemical sensing. Herein, the range of application of photonic MOFs is extended to local thermal and photothermal sensing by integrating them into a new architecture: MOF photonic balls. Micrometric‐sized photonic balls are made of monodispersed MOFs colloids that are self‐assembled via spray‐drying, a low‐cost, green, and high‐throughput method. The versatility of the process allows tuning the morphology and the composition of photonic balls made of several MOFs and composites with tailored optical properties. X‐ray nanotomography and environmental hyperspectral microscopy enable analysis of single objects and their evolution in controlled atmosphere and temperature. Notably, in presence of vapors, the MOF photonic balls act as local, label‐free temperature probes. Importantly, compared to other thermal probes, the temperature detection range of these materials can be adjusted "on‐demand." As proof of concept, the photonic balls are used to determine local temperature profiles around a concentrated laser beam. More broadly, this work is expected to stimulate new research on the physical properties of photonic MOFs providing new possibilities for device fabrication. Abstract : Metal–organic framework (MOF) photonic balls are fabricated by self‐assembly of MOF colloids into microdroplets via spray‐drying, a low‐cost, green, and high‐throughput method. The versatility of the process allows tuning of the morphology and the composition of materials with tailored photonic properties. MOF photonic balls can act as local, label‐free (photo) thermal probes that enable determination of sub‐millimeter temperature gradients.